KONTRIBUSI GURU PAI TERHADAP PEMBENTUKKAN MORAL SISWA MELALUI PROGRAM KEAGAMAAN DI SMPN 1 DIWEK JOMBANG - Galang Dani Prasetyo; Khoirul Umam (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This article describes the role of Islamic Education (PAI) teachers when fostering the morals of students using the implementation of religious program at SMPN 1 Diwek Jombang. PAI teachers not only serve as presenters, but also play a role as counselors in shapping students’ characters. In the midst of the challenges of modern times, especially the negative influence of social media, moral coaching is an important component in the world of education. This study uses a qualitative approach with a descriptive method, and data is obtained by observasion through observation and interviews. The result of the study prove that religious activities such as congregational prayers, recitation of the Qur’an, and istighosah contribute positively to shaping student’ personalities. However, there are still obstacles such as low student motivation and limited supporting facilities. Therefore, solid collaboration between teachers, students, and school is needed to optimize the implementation of this program in a sustainable manner